An exclusive hand protection device made of fused deposition modelling process using poly (lactic acid) polymer. (2022) - Thamizh Selvan, S.; Mohandass, M.; Kumar vairavel, Dinesh; Sethu Ramalingam, P.; Mayandi, K.; Joe Patrick Gnanaraj, S.; Appadurai, M.
Abstract: The world has been hit hardest by a type of Severe Acute Respiratory Syndrome (SARS) virus called corona. This vulnerability did not leave all the superpowers in the world. The virus, is spread through coughs and sneezes. It is also spread by touching objects or parts of an infected person. For this reason, it is considered an infectious disease. It is very difficult to protect ourselves from such a contagious disease. But the World Health Organization (WHO) says there are certain guidelines to follow. The first way is to prevent the spread of COVID-19 social infection by adhering to social spaces (i.e. 2 m intervals). Second, we can protect ourselves by using appropriate safety equipment. We can also protect ourselves from the COVID-19 virus by using sanitizers or soaps. So this study focuses on a 3D-printed hand protection device for COVID- 19 infection prevention. The design, fabrication, and testing of the gadget were all successful. Thus, a low-cost and efficient device made by eco-friendly Poly Lactic Acid (PLA) polymer material and may be utilized to operate some potentially susceptible and highly infectious surfaces in a variety of public areas, where touching and using particular components is common and frequent (eg door handles, electrical switches, ATM machines).